Analisis Kebijakan Badan Tenaga Atom Internasional atas Persetujuan Pembuangan Limbah Nuklir Fukushima Berdasarkan Prinsip Kehati-hatian - Tasya Fainurnissa; Sri Wartini (Fakultas Hukum Universitas Islam Indonesia, 2024)
This research is motivated by policy International Atomic Energy Agency (IAEA) on approval of Japan's Fukushima nuclear waste. The aim of this research is to find out whether the policy regarding the approval of Fukushima waste disposal by IAEA is in accordance with the precautionary principle, and what are the legal implications of the policy IAEA against Japan in granting permits to dispose of Fukushima waste. This research method uses normative legal research, namely research that relies on applicable legislation and is related to the main problem. The approach method used in this research is the statutory method, the conceptual method, and the sociological method,. Data collection techniques were carried out through library study research methods and analysis techniques using descriptive analysis methods. With this method the author reached the conclusion in this research that IAEA has implemented the precautionary principle by implementing 10 international safety standards and processing nuclear waste using methodsAdvanced Liquid Processing System. Additionally, If there is a serious impact on the human and environment, Tokyo Electric Power (TEPCO) and Japanese government must be responsible.